Family of odd point non-stationary subdivision schemes and their applications - Abdul Ghaffar; Zafar Ullah; Mehwish Bari; Kottakkaran Sooppy Nisar; Dumitru Baleanu (Advances in Difference Equations, 2019)
Abstract The (2s−1) $(2s-1)$-point non-stationary binary subdivision schemes (SSs) for curve design are introduced for any integer s≥2 $s≥ 2$. The Lagrange polynomials are used to construct a new family of schemes that can reproduce polynomials of degree (2s−2) $(2s-2)$. The usefulness of the schemes is illustrated in the examples. Moreover, the new schemes are the non-stationary counterparts of the stationary schemes of (Daniel and Shunmugaraj in 3rd International Conference on Geometric Modeling and Imaging, pp. 3–8, 2008; Hassan and Dodgson in Curve and Surface Fitting: Sant-Malo 2002, pp. 199–208, 2003; Hormann and Sabin in Comput. Aided Geom. Des. 25:41–52, 2008; Mustafa et al. in Lobachevskii J. Math. 30(2):138–145, 2009; Siddiqi and Ahmad in Appl. Math. Lett. 20:707–711, 2007; Siddiqi and Rehan in Appl. Math. Comput. 216:970–982, 2010; Siddiqi and Rehan in Eur. J. Sci. Res. 32(4):553–561, 2009). Furthermore, it is concluded that the basic shapes in terms of limiting curves produced by the proposed schemes with fewer initial control points have less tendency to depart from their tangent as well as their osculating plane compared to the limiting curves produced by existing non-stationary subdivision schemes.